PENGARUH AIR KELAPA MUDA TERHADAP PERTUMBUHAN KALUS SECARA IN VITRO DUA VARIETAS TANAMAN TEBU (Saccaharum officinarum L.) - Abdullah, Abdullah; Lestari, Cindy; Numba, Sudirman (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2024)
This work aimed to study the in vitro effect of young coconut water in Murashige and Skoog (MS) media on callus growth of two varieties of sugarcane (Saccaharum officinarum L.). This research was conducted at the Tissue Culture Laboratory of the research and development unit of PTPN XIV Camming Sugar Factory, Bone Regency, and using a Completely Randomized Design (CRD). The treatment consisted of young coconut water concentrations of 0%, 10%, 20%, and 30%, as well as two varieties of sugarcane, namely PSBM 901 and Kidang Kencana. Data were analyzed statistically by F-test and BNJ α 0.5%. The results showed that the growth of callus from sugarcane explants of the Kidang Kencana variety was better than that of the PSBM 901 variety in the basic culture medium of Murashige Skoog(MS) with the addition of various concentrations of coconut water. The addition of 30% young coconut water into the basic medium of tissue culture of Murashige Skoog (MS) can increase the callus growth of sugarcane explants of PSBM 901 and Kidang Kencana varieties.